Crude Oil Pipeline Vandalism and its Effects on Crude-Oil Terminals Operations in Nigeria: A Study of Bonny Crude Oil Terminal Operations - Nchinney, Dimla Joel (Kashere Journal of Politics and International Relations, 2025)
The Nigerian Oil sector being the major source of revenue to the nation has over the years suffered series of challenges as a result of frequent pipeline vandalism by thieves, thereby affected the volume of quantity of crude oil exploration. This paper examines the menace of crude oil vandalism in one of the major crude oil terminals in Nigeria, the Bonny Terminal. It adopts a qualitative methodology through the use of both primary and secondary sources of data collection. Primary data were generated through Key Informant Interview (KII) and secondary data were utilized through books, journals, articles, conferences papers, government documents, among others. It also uses frustration–aggression theory to analyze reasons for people of the area engaging in these criminal acts. The findings reveal that, there is significant relationship between the pipeline vandalism and effective functioning of bonny terminal. Equally, part of the modes of operation by the vandals is the use of equipment to puncture the pipelines. They have experts who are engineers that use a hose to link the oil from underground. They cover it so that it will not be detected, and then connect the hose to a far place where the refining takes place. They also have a big boat that is solely used for transporting oil to its selling destination, among other modus operandi. Consequently, it is recommended that, a robust community policing should be established with local residents in maintaining safety of pipelines which would complement the patrol-works of the security agencies and oil companies